Resistance of silicon carbide to penetration by a tungsten carbide cored projectile - Roberson, Colin J.; Hazell, Paul J. (Cranfield University, 2003)
Silicon carbide is well known as being a ceramic that can be employed as part of an effective armour solution to defeat small arms ammunition. Its relatively high hardness and ability to accommodate large plastic strains at high confining pressures lend itself to offering sufficient resistance to defeat tungsten carbide cored projectiles. In this paper, the 7.62 × 51mm FFV*† round consisting of a tungsten carbide core (Hv 1200) and copper gilding jacket was fired at a variety of thicknesses and types of silicon carbide. The results suggest that it is not only the type of silicon carbide that is important in the design of the armour solution but also a critical thickness that is necessary to sufficiently resist and damage the round. This paper will also draw conclusions on the effectiveness of the manufacturing routes of silicon carbide for armour solutions. This paper will be of interest to armour system designers and manufacture
Proceedings of the Ceramic Armor and Armor Systems symposium held at the 105th Annual Meeting of the American Ceramic Society, 27-30 April 2003, in Nashville, TN, USA
Keywords: ceramic armour; penetration mechanisms; tungsten carbide penetrator.